A New Method for Quantifying Outcomes in Discounting. - Smits, Rochelle R.; Newquist, Matthew H. (My University, 2009)
Discounting has been defined as a decrease in the subjective value of an outcome as the delay to or uncertainty of receiving the outcome increases. Previous research has not quantified consumable and non-consumable outcomes in similar units. The purpose of the present study is to validate an approach to quantifying various rewards that allows for the comparison of qualitatively different rewards on a quantitatively similar scale.
Color poster with text and graphs describing research conducted by Rochelle R. Smits and Matthew H. Newquist, advised by Daniel D. Holt.
Keywords: Delay of gratification; Choice (Psychology); Reward (Psychology); Posters